2006
DOI: 10.1042/cs20050363
|View full text |Cite
|
Sign up to set email alerts
|

Increased visfatin concentrations in women with gestational diabetes mellitus

Abstract: The recently discovered adipocytokine visfatin has insulin-like properties. It lowers blood glucose and improves insulin sensitivity; however, clinical data on visfatin are limited. To evaluate the role of visfatin in GDM (gestational diabetes mellitus), we determined visfatin levels in women with GDM and in healthy pregnant controls. Furthermore, visfatin concentrations were investigated longitudinally during pregnancy and after delivery in a subgroup of women with GDM. Blood for measurement of visfatin and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
132
2
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(152 citation statements)
references
References 26 publications
11
132
2
7
Order By: Relevance
“…Therefore, mathematical models (HOMA vs IRI) used to calculate IR indices in pregnancy may give discrepant results, and thereby a relationship between visfatin and calculated IR indices. Very recently, unlike our findings and those by Krzyzanowska et al [9], Chan et al [10] have reported lower visfatin levels in women of Chinese origin with GDM. The precise reason for these differences is unclear.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Therefore, mathematical models (HOMA vs IRI) used to calculate IR indices in pregnancy may give discrepant results, and thereby a relationship between visfatin and calculated IR indices. Very recently, unlike our findings and those by Krzyzanowska et al [9], Chan et al [10] have reported lower visfatin levels in women of Chinese origin with GDM. The precise reason for these differences is unclear.…”
Section: Discussioncontrasting
confidence: 98%
“…During the preparation of our paper, Krzyzanowska et al [9] reported raised visfatin levels in GDM. In contrast to their data, we found a significant correlation between visfatin and fasting insulin and HOMA.…”
Section: Discussionmentioning
confidence: 84%
“…The number of participants, gestational age at enrolment, BMI, and the specificity of the immunoassays applied differ between all the above studies. Gestational diabetes mellitus is a state of temporary insulin resistance, and elevated visfatin concentrations might counteract high glucose and insulin levels [52]. Thus, elevated maternal visfatin concentrations in GDM at 2nd trimester may reflect an impairment of visfatin function in target tissues, dysregulation of biosynthesis, or a response to hyperglycemia [52].…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus is a state of temporary insulin resistance, and elevated visfatin concentrations might counteract high glucose and insulin levels [52]. Thus, elevated maternal visfatin concentrations in GDM at 2nd trimester may reflect an impairment of visfatin function in target tissues, dysregulation of biosynthesis, or a response to hyperglycemia [52]. On the other hand, TNF-a is known to enhance visfatin expression in human placental cells [53].…”
Section: Discussionmentioning
confidence: 99%
“…Data available on visfatin levels in patients with GDM are also controversial. To date, two previous studies (11,12) reported increased visfatin concentrations in GDM, whereas others (13,14) showed that GDM is associated with decreased visfatin concentrations. Since visfatin is an adipocytokine that is associated with glucose homeostasis, we hypothesized that maternal visfatin concentrations might be altered in pregnant women with GDM in the third trimester, which is an advanced state of insulin resistance.…”
Section: Introductionmentioning
confidence: 96%